External Conflict as a Form of Characterisation: An Analysis of How to Break a Dragon’s Heart by Cressida Cowell - Wahlroos, Viljami (My University, 2026)
Conflict is one important element in storytelling. It plays a role in many parts of a story, but one of the most crucial ones is characterisation. This paper looks at how that applies to the novel How to Break a Dragon’s Heart (2009) by analysing what the different kinds of conflicts of the novel reveal about the characters involved in them, and the kinds of methods that are used to do so. As the book in question is somewhat part of a tonal shift in the series, with some conflicts having a lighter tone versus some having a darker tone a particular interest is seeing if and how characterisation is different between those two types of conflicts. The analysis finds that across all the conflicts, a common way to add to characterisation is the method characters use to try to solve the conflict.
Keywords: conflict; tone; characters; literature; How to Break a Dragon’s Heart.